Amphiphilic polypyridyl ruthenium complexes: synthesis, characterization and aggregation studies - Bhand, Sujit; Lande, Dipali N.; Pereira, Eulalia; Gejji, Shridhar P.; Weyhermueller, Thomas; Chakravarty, Debamitra; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Polyhedron, 2019)
{Synthesis and characterization of five amphiphilic ruthenium(11) complexes of the type [Ru(Cn)(3)]center dot(PF6)(2) (Cn = 4,4'-dialkyl-2,2'-bipyridine
Keywords: 2; 2 `-bipyridine; Aggregation; Amphiphilic ligand; Metallosurfactant; Ruthenium complexes

Design and synthesis of piano-stool ruthenium(II) complexes and their studies on the inhibition of amyloid ? (1-42) peptide aggregation - Singh, Sain; Navale, Govinda R.; Agrawal, Sonia; Singh, Haobam Kisan; Singla, Labhini; Sarkar, Dhiman; Sarma, Manabendra; Choudhury, Anghuman Roy; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Misfolding , protein aggregation have been linked to numerous human neurodegenerative disorders such as Alzheimer's, prion , Parkinson's diseases. Ruthenium (Ru) complexes have received considerable attention in studying protein aggregation due to their interesting photophysical and photo properties. In this study, we have synthesized the novel Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6](Ru-1), and [Ru(p-cymene)Cl(L-2)][PF6](Ru-2)) and investigated their inhibitory activity against the bovine serum albumin (BSA) aggregation and the A beta 1-42 peptides amyloid formation. Several spectroscopic methods were used to characterize these complexes, and the molecular structure of the complex was determined by X-ray crystallography. Amyloid aggregation and inhi-bition activities were examined using the Thioflavin-T (ThT) assay, and the secondary structures of the protein were analyzed by circular dichroism (CD) spectroscopy and transmission electron microscopy (TEM). The cell viability assay was carried out on the neuroblastoma cell line, revealing that the complex Ru-2 showed better protective effects against A beta 1-42 peptide toxicity on neuro-2a cells than the complex Ru-1. Molecular docking studies elucidate the binding sites and interactions between the Ru-complexes and A beta 1-42 peptides. The exper-imental studies revealed that these complexes significantly inhibited the BSA aggregation and A beta 1-42 amyloid fibril formation at 1:3 and 1:1 molar concentrations, respectively. Antioxidant assays demonstrated that these complexes act as antioxidants, protecting from amyloid-induced oxidative stress. Molecular docking studies with the monomeric A beta 1-42 (PDB: 1IYT) show hydrophobic interaction, and both complexes bind preferably in the central region of the peptide and coordinate with two binding sites of the peptide. Hence, we suggest that the Ru-based complexes could be applied as a potential agent in metallopharmaceutical research against Alzheimer's disease.
Keywords: Aggregation; Amyloid ?(1-42) peptide; DFT computation; Fibrillization; Molecular docking; Ruthenium complexes